Pragian and lower Emsian (Lower Devonian) conodonts from Liujing, Guangxi, South China. Issue 2 (2nd April 2016) - Lu, Jian-Feng; Qie, Wen-Kun; Chen, Xiu-Qin
Abstract : LU, J.-F., QIE, W.-Q. & CHEN, X.-Q., July 2016. Pragian and lower Emsian (Lower Devonian) conodonts from Liujing, Guangxi, South China. Alcheringa 40, xxx–xxx. ISSN 0311-5518. Lower Devonian (Pragian and Emsian) conodonts are described from the Liujing section in Guangxi, South China, highlighting the phylogeny of early polygnathids and establishing the basis for faunal correlations with deposits throughout the world. Records of Eognathodus kuangi sp. nov. and E. nagaolingensis Xiong increase the biodiversity of the Pragian eognathodids in South China and represent intermediate stages and probably the latest eognathodids in the evolutionary succession from Eognathodus to Polygnathus . During this evolutionary succession, the degeneration of the sulcus (or the flattening of the upper platform surface) is the most important morphological change, especially in the eognathodid lineage. Polygnathus trilinearis, P. pireneae and P. sokolovi are recognized together for the first time in South China. The contemporaneous occurrences of the kitabiformis and sokoloviformis morphs of P. pireneae with P. sokolovi and their respective similarities to P. kitabicus and P. sokolovi suggest that the latter two species are phylogenetically linked with P. pireneae . Evidence from the Liujing section also favours Polygnathus probably having evolved from Eognathodus in a tropical or subtropical area. Jian-feng Lu* [ lujfivan@sina.cn ] and Xiu-qin Chen [ xqchen@nigpas.ac.cn ], Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China; Wen-Kun Qie [ wkqie@nigpas.ac.cn ], Key Laboratory of Economic Stratigraphy and Palaeogeography, Nanjing Institute of Geology and Palaeontology, 39 East Beijing Road, Nanjing 210008, PR China. *Also affiliated with University of Chinese Academy of Sciences, Beijing 100049, PR China.